Effects of Potassium Supply in Nutrient Solution on Water and Nutrient Absorption of Substrate-Grown Tomato Plants - Jinxiu Song; Rong Zhang; Bingyan Fu; He Chen; Xiaoming Song; Gaoqiang Lv; Rongqiang Zhang (Horticulturae, 2025)
Potassium (K+) functions as a critical “regulator” and “quality element” in plants, with its physiological roles varying across developmental stages. To clarify the effects of different K+ amounts in nutrient solution on water and nutrient absorption characteristics and potassium utilization efficiency in substrate-grown tomato, a controlled experiment was conducted in a climate-regulated solar greenhouse using “Saint Ness” tomato as the plant material. Four K+ supply levels (1, 4, 8, and 16 mmol/L, designated as K1, K4, K8, and K16 treatment, respectively) were tested to systematically evaluate the responses of tomato plants at different growth stages in terms of water and nutrient absorption capacity, potassium physiological efficiency (KPE), and potassium utilization efficiency (KUE). The results showed that water absorption capacity did not differ significantly among treatments during the vegetative growth stage. However, during the reproductive stage, the K8 treatment exhibited the highest water absorption capacity (47.05 kg/plant) and water absorption efficiency (84.6%). In addition, K8 significantly promoted the coordinated uptake of K+, nitrogen, phosphorus, calcium, and magnesium, with a total potassium absorption capacity of 7.2 g/plant and a potassium absorption efficiency of 79.1%. In contrast, excessive K+ supply (16 mmol/L) increased total potassium absorption capacity (5.09 g/plant) but led to a marked decline in physiological efficiency (by 27.9%) and water absorption efficiency (by 10.3%) due to luxury consumption and substrate-induced salt stress. Insufficient K+ levels (1–4 mmol/L) also restricted root-mediated water and nutrient flux. The study further revealed a dose-dependent and stage-specific pattern in water and potassium absorption. Therefore, an appropriate K+ supply of 8 mmol/L not only improved the plant’s absorption capacity for water and nutrients and potassium utilization efficiency but also maintained ionic balance among essential nutrients. These findings provide a theoretical basis for precision water and fertilizer integration strategies in substrate-cultivated tomato production under greenhouse conditions.